ACUTE TOXICITY STUDY OF ETHANOLIC EXTRACT OF SOLANUM INCANUM. L FRUIT - INDHUMATHI.T; S.MOHANDASS; SHIBI.A (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Solanaceae is a large plant family containing two thousand and three hundred, nearly half of which belong to single genus, Solanum. Solanum incanum is a species of nightshade that is native to north western Africa and the Middle East (USDA, 2006). The leaves are consumed as leafy vegetables, while the fruits are extensively used in Kenya for the treatment of cutaneous mycotic infections and other pathological conditions. This study was aimed to determine the toxicity profile of the ethanolic extract of Solanum incanum fruit by determining its effects after administration in female mice. The acute toxicity studies were carried out based on OECD guidelines 423 and fixed dosage studies was adopted where the limit dose is 2000mg/kg body weight of test animal. The animals were orally administered a single dose of 100, 250, 500, 750, 1000 and 2000 mg/kg body weight. Signs of toxicity and mortality were noted after 1, 4 and 24h of administration of the extract for 14 days. The highest dose administered (2000mg/kg body weight) did not produce mortality or changes in general behavior of the test animals. These results indicate the safety of the oral administration of ethanol extract of Solanum incanum. Â KEYWORDS: Acute toxicity, Solanum incanum, ethanolic extract, mice.